The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15252/embr.201948692
|View full text |Cite
|
Sign up to set email alerts
|

ABCA12 regulates insulin secretion from β‐cells

Abstract: Dysregulation of lipid homeostasis is intimately associated with defects in insulin secretion, a key feature of type 2 diabetes. Here, we explore the role of the putative lipid transporter ABCA12 in regulating insulin secretion from β‐cells. Mice with β‐cell‐specific deletion of Abca12 display impaired glucose‐stimulated insulin secretion and eventual islet inflammation and β‐cell death. ABCA12's action in the pancreas is independent of changes in the abundance of two other cholesterol transporters, ABCA1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…This is supported by the reduced number of insulin granules docked at the plasma membrane in -cells from isolated islets from -ROCK1 -/mice, which is associated with a decrease in the first phase of insulin release during glucose stimulation. Consistent with this view, previous reports link several proteins such as TRB3 [36], ABCA12 [38] and LKB1 [39] with modulating insulin granules and plasma membrane docking dynamics in the regulation of GSIS. The mechanism(s) underlying insulin granules mobilization could involve in F-actin remodeling in response to glucose stimulation [40].…”
Section: Discussionsupporting
confidence: 66%
“…This is supported by the reduced number of insulin granules docked at the plasma membrane in -cells from isolated islets from -ROCK1 -/mice, which is associated with a decrease in the first phase of insulin release during glucose stimulation. Consistent with this view, previous reports link several proteins such as TRB3 [36], ABCA12 [38] and LKB1 [39] with modulating insulin granules and plasma membrane docking dynamics in the regulation of GSIS. The mechanism(s) underlying insulin granules mobilization could involve in F-actin remodeling in response to glucose stimulation [40].…”
Section: Discussionsupporting
confidence: 66%
“…Lipids play important roles in ISG maturation. The cholesterol content of insulin granules is high, at least in part through the action of granule-localized ABC cholesterol transporters [64,65]. β-Cells lacking the ABCG1/ ABCA12 cholesterol transporters or treated with cholesterol synthesis inhibitors present with enlarged ISG and exhibit reduced glucose-stimulated insulin secretion [64][65][66].…”
Section: Ca 2+mentioning
confidence: 99%
“…The cholesterol content of insulin granules is high, at least in part through the action of granule-localized ABC cholesterol transporters [64,65]. β-Cells lacking the ABCG1/ ABCA12 cholesterol transporters or treated with cholesterol synthesis inhibitors present with enlarged ISG and exhibit reduced glucose-stimulated insulin secretion [64][65][66]. The mechanism of cholesterol action is not clear, but it has been shown that cholesterol transport is needed to protect newly formed ISG against lysosomal degradation [28].…”
Section: Ca 2+mentioning
confidence: 99%
“…Disease development was profiled using a custom-made skin-related Nanostring GX array (see Data S1 ) which confirmed an ∼50% loss of Abca12 transcript and a reduction in Abca1 mRNA consistent with previous reports ( Figure 3 H). 12 Using a previously characterized antibody, 15 no ABCA12 protein was detectable by immunofluorescence analysis, suggesting that the persistent transcript was non-functional ( Figure 3 I). Of the 95 genes included in the Nanostring array, 57 were found to be significantly dysregulated upon Abca12 deletion, including the downregulation of differentiation markers ( Krt10 and Lor ) and the upregulation of wounding and proliferation markers ( Krt5 , Krt14 , Krt6a/b , and Krt16 ) ( Data S1 ).…”
Section: Resultsmentioning
confidence: 98%